From SARS and MERS CoVs to SARS‐CoV‐2: Moving toward more biased codon usage in viral structural and nonstructural genes. Issue 6 (16th March 2020) - Kandeel, Mahmoud; Ibrahim, Abdelazim; Fayez, Mahmoud; Al‐Nazawi, Mohammed
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is an emerging disease with fatal outcomes. In this study, a fundamental knowledge gap question is to be resolved by evaluating the differences in biological and pathogenic aspects of SARS‐CoV‐2 and the changes in SARS‐CoV‐2 in comparison with the two prior major COV epidemics, SARS and Middle East respiratory syndrome (MERS) coronaviruses. Methods: The genome composition, nucleotide analysis, codon usage indices, relative synonymous codons usage, and effective number of codons (ENc) were analyzed in the four structural genes; Spike (S), Envelope (E), membrane (M), and Nucleocapsid (N) genes, and two of the most important nonstructural genes comprising RNA‐dependent RNA polymerase and main protease (Mpro) of SARS‐CoV‐2, Beta‐CoV from pangolins, bat SARS, MERS, and SARS CoVs. Results: SARS‐CoV‐2 prefers pyrimidine rich codons to purines. Most high‐frequency codons were ending with A or T, while the low frequency and rare codons were ending with G or C. SARS‐CoV‐2 structural proteins showed 5 to 20 lower ENc values, compared with SARS, bat SARS, and MERS CoVs. This implies higher codon bias and higher gene expression efficiency of SARS‐CoV‐2 structural proteins. SARS‐CoV‐2 encoded the highest number of over‐biased and negatively biased codons. Pangolin Beta‐CoV showed little differences with SARS‐CoV‐2 ENc values, compared with SARS, bat SARS, and MERS CoV. Conclusion: Extreme bias and lower ENc values of SARS‐CoV‐2, especially in Spike, Envelope, and Mpro genes, are suggestive for higher gene expression efficiency, compared with SARS, bat SARS, and MERS CoVs.